2016
DOI: 10.1002/2211-5463.12099
|View full text |Cite
|
Sign up to set email alerts
|

Gene transcription and steviol glycoside accumulation in Stevia rebaudiana under polyethylene glycol‐induced drought stress in greenhouse cultivation

Abstract: Stevia rebaudiana is a sweet herb of the Astraceae family, which is cultivated for the natural sweeteners it contains. The aim of this study was to assess the effect of drought, simulated by the application of polyethylene glycol (5%, 10%, and 15% w/v), on the content of steviol glycosides (SVglys) and transcription levels of six genes involved in the biosynthesis of these natural sweeteners. The transcription levels of ent‐kaurene synthase, ent‐kaurene oxidase, ent‐kaurenoic acid hydroxylase, and three UDP‐de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 29 publications
0
29
0
1
Order By: Relevance
“…Furthermore, in Arabidopsis , ectopic over-expression of UGT74E2 increased the tolerance to salinity and drought stress, and reduced the water loss in plants 38 , while 11 UGTs were up-regulated in response to H 2 O 2 stress in catalase-deficient plants 39 . Recently, UGT85C2 , UGT74G1 , and UGT76G1 were shown to be downregulated under polyethylene glycol-induced drought stress in Stevia rebaudiana 40 . The role of abscisic acid (ABA) in mediating drought stress has been extensively studied and several UGTs have been functionally characterized for ABA-glucose ester formation 41 44 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in Arabidopsis , ectopic over-expression of UGT74E2 increased the tolerance to salinity and drought stress, and reduced the water loss in plants 38 , while 11 UGTs were up-regulated in response to H 2 O 2 stress in catalase-deficient plants 39 . Recently, UGT85C2 , UGT74G1 , and UGT76G1 were shown to be downregulated under polyethylene glycol-induced drought stress in Stevia rebaudiana 40 . The role of abscisic acid (ABA) in mediating drought stress has been extensively studied and several UGTs have been functionally characterized for ABA-glucose ester formation 41 44 .…”
Section: Introductionmentioning
confidence: 99%
“…Stevia cultivation in Iran with a hot and dry weather faces some problems associated with drought stress. Previous studies have shown that S. rebaudiana was not resistant to water stress under in vitro and greenhouse conditions (Hajihashemi and Ehsanpour 2013; Hajihashemi and Geuns 2016;Hajihashemi and Ehsanpour 2014). Hence, the most practical approach for increasing Stevia yield in drought condition is to study on features involved in Stevia cell response to drought stress.…”
Section: Introductionmentioning
confidence: 99%
“…The enzymes of kaurene oxidase (KO) and kaurene synthase (KS) involve in biosynthesis of both GA and SV molecules (Brandle and Telmer 2007). It is reported that GA treatment significantly increased the transcription of ent-KS1, ent-KO in S. rebaudiana, while the GA biosynthesis inhibitor, paclobutrazol (PBZ) reduced their transcriptions (Hajihashemi and Geuns 2016;.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations